Detection of Kidney Stone in MRI Images Using Ideal Filter (International Journal of Scientific Research and Management (IJSRM), 2017)
A Filter method is introduced in this paper for efficient speckle suppression and detection of calculi in sonographic images of the kidney.Wavelets are developed in applied mathematics for the analysis of multiscale image structures. The aim of this project is to analysesand to provide most significant content descriptive parameters to identify and classify the kidney stones with ultrasound scan. Speckle filtering is a critical preprocessing step. Ideal Filter provides an appropriate basis for separating the speckle noise from an image. Filtering is used for unsupervised image segmentation.The statistical features are extracted by decomposing the kidney stone images into different frequency sub-bands using wavelet transform